Cardio Phenotypic Potential of Mesenchymal Stem Cells. Issue 3 (4th March 2021) - Peterson, Karen M.; Franchi, Federico; Olthoff, M.; Paulmurugan, Ramasamy; Rodriguez‐Porcel, Martin
Abstract: Cell therapy is being investigated as a powerful intervention to ameliorate the consequences of coronary artery disease. Among the different stem cell options, mesenchymal stem cells (MSCs) are particularly attractive due to their high availability, as well as immune‐privileged status. However, it is still unclear whether mesenchymal stem cells can acquire cardiomyogenic characteristics after they are transplanted to the myocardium. In this article, we outline protocols that illustrate the plasticity of MSCs and their ability to acquire cardiogenic characteristics when they are in an ischemic‐like environment, as typically encountered after transplantation into the ischemic heart. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Isolation of mesenchymal stem cells (MSCs) Support Protocol 1 : Characterization of MSCs by flow cytometry Basic Protocol 2 : Isolation of neonatal cardiomyoctes (NCMs) Support Protocol 2 : Characterization of NCMs Basic Protocol 3 : Cardiogenic plasticity of MSCs under ischemic‐like conditions Support Protocol 3 : Characterization of the cardiomyogenic potential of MSCs